2013
DOI: 10.1002/gps.4012
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of suicidal ideation in older individuals receiving home‐care services

Abstract: Preventive strategies focusing on depression, social support, and disability should be emphasized during encounters with older people receiving home-care services.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0
2

Year Published

2014
2014
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 42 publications
(67 reference statements)
0
13
0
2
Order By: Relevance
“…Previous studies on suicide ideation in elderly individuals have mainly focused on family relationships (Song, Son, & Park, 2010), socio-economic support (Goodwin, Kroenke, Hoven, & Spitzer, 2003;Park et al, 2014), and physical and mental health status (Park, 2014;Yang & Jo, 2013). Some studies (Kim et al, 2010;Seomun & Lee, 2011) have reported that depression is the most important factor associated with elderly suicide ideation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies on suicide ideation in elderly individuals have mainly focused on family relationships (Song, Son, & Park, 2010), socio-economic support (Goodwin, Kroenke, Hoven, & Spitzer, 2003;Park et al, 2014), and physical and mental health status (Park, 2014;Yang & Jo, 2013). Some studies (Kim et al, 2010;Seomun & Lee, 2011) have reported that depression is the most important factor associated with elderly suicide ideation.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, studies of suicide often focus on actual suicide attempts as well as suicide ideation (Harwood & Jacoby, 2000). Therefore, any individual expressing suicidal thoughts or intentions must be treated with caution (Dong, Chen, Wong, & Simon, 2014;Park et al, 2014); therefore, it is crucial to gain a better understanding of suicide ideation among the elderly and the factors that are related to suicide ideation in this population.…”
Section: Introductionmentioning
confidence: 99%
“…Research has identified many factors associated with older adult suicidal ideation and behavior. One of the most salient is psychopathology, particularly major depression . Research in the United States, South Korean, Brazilian, and Australian older adults suggests that psychological distress generally and major depression specifically account for the most variance in models examining suicidal ideation.…”
Section: Introductionmentioning
confidence: 99%
“…Aus anderen Untersuchungen sind weitere Risikofaktoren wie Leben in einer ländlichen Gegend, Verlust des Partners, Behinderung, mangelnde soziale Unterstützung und das Fehlen einer Pharmakotherapie bei Vorliegen einer Depression bekannt [8,10,13]. Zudem korreliert eine geringere Unterstüt-zung durch Familienmitglieder mit einem höheren Auftreten von suizidalen Absichten [11]. Es ist außerdem wichtig, ältere Menschen über bestehende Hilfsangebo- te aufzuklären, da diese so gut wie nie von allein professionelle Hilfe aufsuchen [5].…”
Section: Risikofaktorenunclassified